1998
DOI: 10.1080/03014469800006672
|View full text |Cite
|
Sign up to set email alerts
|

Changes in growth patterns in Zagreb school children related to socioeconomic background over the period 1973–1991

Abstract: The purpose of this paper is to present the changes in growth patterns in different socio-economic classes of Zagreb school children over the period 1973-1991. Classes are defined by parental occupation. Surveys were performed in 1973, 1982 and 1991 covering 8938, 10700, and 7400 examinees aged 7 to 19 respectively. In all three observed generations boys and girls belonging to social group I (nonmanual workers' families) were taller than their peers in group III (manual workers' families). Differences were mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 13 publications
2
6
0
4
Order By: Relevance
“…It had been thought that in industrialized nations the trend for increased size and earlier maturation of children had stopped or slowed down considerably, possibly due to a moderation of social, medical, and economic changes (Hauspie et al, 1996(Hauspie et al, , 1997Eveleth et al, 1979;Lhotska et al, 1994;Prebeg et al, 1995;Prebeg, 1998). The present results are in accord with Herman-Giddens et al (1997), who suggested that earlier puberty continues to be a real phenomenon.…”
Section: Discussionsupporting
confidence: 85%
“…It had been thought that in industrialized nations the trend for increased size and earlier maturation of children had stopped or slowed down considerably, possibly due to a moderation of social, medical, and economic changes (Hauspie et al, 1996(Hauspie et al, , 1997Eveleth et al, 1979;Lhotska et al, 1994;Prebeg et al, 1995;Prebeg, 1998). The present results are in accord with Herman-Giddens et al (1997), who suggested that earlier puberty continues to be a real phenomenon.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, inequalities in childhood height are of particular interest. Evidence to date suggests that social inequalities in childhood height may have reduced in magnitude in recent decades, [19][20][21][22] although they still exist in several countries. 20 [23][24][25] In order to establish whether inequalities in height have reduced in recent years, we compare height inequalities in two generations during a period of secular increase.…”
mentioning
confidence: 99%
“…This is probably because, in many European countries, secular trend has started much earlier and are coming close to a halt while India is only recently progressing. The comparison of decadal changes reported in different countries/populations, thus, becomes difficult as it is known to vary due to numerous factors such as time (21), age, race (22), region (23), social class (24), and parents’ education (25). …”
Section: Discussionmentioning
confidence: 99%